Consumer protection in the supply of services:a comparative study between the Consumer Protection Act 1999 and Islamic law - Abu Bakar, Elistina; Amin, Naemah (IIUM Press, 2010)
The Consumer Protection Act 1999 (CPA) that came into force on 15 November 1999 represents a milestone in consumer protection in Malaysia.It has several important provisions, some of which are more beneficial than those found in the law of contract and law of tort since its objective is specifically to protect the interest of consumers. The statute is applicable to both goods and services but the provisions on services are very important because previously the laws regulating the supply of services seem to be left behind compared to those regulating goods.The aim of this paper is to examine the relevant provisions of the CPA and make a comparative study with the protection available under the Islamic law of muamalat. The central discussions are on section 53, section 54 and part 1X of the CPA since they deal specifically with the supply of services. The liabilities of the service providers are scrutunised as well as consumers' rights of redress.